Factors Affecting Green Purchase Behavior of AMDK Aqua Life on College Student Consumers in Surakarta City - Evy Nuryudhiani; Lobes Herdiman; Susy Susmartini (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2022)
The fundamental accomplishment of the Sustainable Packaging Coalition (SPC) concept is to replace unnecessary plastics used in the packaging and towards a green packaged product concept that is sustainable and environmentally friendly. Aqua Life's innovative bottled water contributes to achieving sustainability with packaging made from recycled and recyclable materials. Consequently, this study extended the Value Attitude Behavior (VAB) model by using the following construct: environmental consciousness, attitudes toward environmental issues, attitudes toward eco-social benefits, green product information, green product quality, availability of desired green packaged products, and green product attributes; to explain consumers’ green purchase behavior. This study was to survey 251 college students in Surakarta city. The data were analyzed using the Partial Least Square-Structural Equation Model (PLS-SEM) method. The results show that environmental consciousness, attitudes toward environmental issues, green product information, availability of desired green packaged products, and green product attribute as a significant predictor